2015
DOI: 10.1007/s12013-015-0705-6
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Nanoparticles Activate Erythrocyte Aggregation and Adhesion to Endothelial Cells

Abstract: Nanoparticles (NPs) are drawing an increasing clinical interest because of their potential use as drug carriers. Recently, a new strategy for elevation of NPs in vivo circulation time has been proposed, specifically, utilizing red blood cells (RBCs) as a carrier for NPs, that are loaded with a drug, by interaction (in vitro) of human RBCs with NPs (RBCNP). This class of delivery set-up, combines advantages of natural RBCs and synthetic biomaterials. Previous studies demonstrated that NPs initiated hemolysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Earlier, it was demonstrated that relatively large NP agglomerates (~0.2 μm) were able to penetrate RBCs through the membrane with no influence on the nature of the NP material 7 . Significant RBC agglutination and stronger adhesion caused by small NPs than larger ones were observed for different types of NPs 810 . Surface properties are considered one of the major factors for the hemocompatibility of NPs.…”
Section: Introductionmentioning
confidence: 96%
“…Earlier, it was demonstrated that relatively large NP agglomerates (~0.2 μm) were able to penetrate RBCs through the membrane with no influence on the nature of the NP material 7 . Significant RBC agglutination and stronger adhesion caused by small NPs than larger ones were observed for different types of NPs 810 . Surface properties are considered one of the major factors for the hemocompatibility of NPs.…”
Section: Introductionmentioning
confidence: 96%
“…The authors showed that the formation of RBC aggregates increased with decreasing particle size and in parallel a distinctly elevated adhesion to endothelial cells was observed. 175 In addition, Barbul et al showed that polystyrene particles with sizes of 27, 45, and 100 nm adsorbed to RBCs led to shape transformations and reduced cell deformability, with the 27 nm particles showing the strongest effect. 176 Furthermore, Xia et al showed the influence of 30 nm polystyrene nanoparticles on the endocytotic pathway in macrophages and human cancer cell lines A549, HePG-2, and HCT116.…”
Section: Impact Of Nanoplastics On Human Healthmentioning
confidence: 99%
“…The presence of this defense system could explain their resistance to the damage induced by nanoparticles, indicating that these cells are not as sensitive to the toxic effects of nanoparticles. However, one of the factors that can influence whether a nanoparticle leads to hemolysis or not is the presence of surfactants [28] and [29] coatings. Surfactants confer different properties to nanomaterials, altering charge, interfacial tension, and becoming an amphiphilic molecule, which reduces the nanomaterial coalescence.…”
Section: Interaction Of Nanomaterials With Red Cellsmentioning
confidence: 99%